Mukhamandapa (front porch) of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Access to the temple is granted through the mukhamandapa (front porch) of the Undeshwar Temple, with steps bordered by depictions of deities. The mukhamandapa is a small hall with low walls along its sides. Atop these walls, four pillars stand at each corner, offering support for the flat roof above.